PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI DENGAN ADANYA PENERAPAN TARGETED ADVERTISING (PERIKLANAN BERTARGET) PADA PENGGUNA MEDIA SOSIAL DI INDONESIA - DUTA PANGESTU FUADDIN NIM. A1011191126 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Targeted advertising is an advertising method created and formed based on data taken from the activities of social media users. Privacy and legal protection are important aspects to consider, as they involve the lifestyle and interaction of people in cyberspace, which is now very significant. Therefore, the authors are interested in researching this matter. The formulation of the problem of this research is